Clinicopathological features and outcomes of kidney allografts in plasma cell‐rich acute rejection: A case series. (2nd July 2018) - Hamada, Aki Mafune; Yamamoto, Izumi; Kawabe, Mayuko; Katsumata, Haruki; Yamakawa, Takafumi; Katsuma, Ai; Nakada, Yasuyuki; Kobayashi, Akimitsu; Koike, Yusuke; Miki, Jun; Yamada, Hiroki; Kimura, Takahiro; et al.
ABSTRACT: Plasma cell‐rich acute rejection (PCAR) is a rare type of acute rejection in renal transplantation. Despite aggressive immunotherapy, approximately 40–60% of patients develop graft loss within 1 year after an episode of PCAR. However, the reason for this outcome remains obscure. This study retrospectively identified six patients with PCAR diagnosed between 2009 and 2015 at a single university hospital. Clinicopathological data were collected. Five of the six patients were male, and mean age at the onset of PCAR was 49.0 ±14.5 years. None of the patients showed overall poor adherence to medication. Mean time to diagnosis was 302 ±234 days post‐transplantation. All patients had preceding or concurrent viral infection. Four patients developed PCAR alone and two patients developed PCAR with antibody‐mediated rejection. One of the six patients showed both severe tubulointerstitial and microvascular inflammation (total of Banff tubulitis 't' + interstitial inflammation 'i' + glomerulitis 'g' + peritubular capillaritis 'ptc' scores >10). This patient had progressive worsening of graft function and re‐initiated dialysis at 74 months after a PCAR episode. In addition, three of the six patients had long‐term recurrence of PCAR. With the recurrence of PCAR, patients with both moderate tubulointerstitial and microvascular inflammation (total of Banff 't' + 'i' + 'g' + 'ptc' scores >6) had progressive worsening of graft function. In summary, the present results suggest that concurrent moderate to severe tubulointerstitial and microvascular inflammation may lead to poor outcomes of graft function after a PCAR episode.